Production of antibacterial hydroxyapatite - İpekoğlu, Mehmet. (Thesis (Ph.D.)-Bogazici University. Institute for Graduate Studies in Science and Engineering, 2011., 2011)
Hydroxyapatite was produced by rapid microwave synthesis method. Effects of microwave power and duration were examined on the powder morphology of the hydroxyapatite powder during the synthesis process and microwave aging was found to be an effective method to produce hydroxyapatite. Silver was added in different amounts to calcium deficient and stoichiometric hydroxyapatite during the synthesis process using microwave, the antibacterial activities of the powders produced were analyzed and silver addition was found to impart antibacterial properties to hydroxyapatite. Hydroxyapatite powders containing different amounts of silver were heat treated at temperatures between 900-1100 °C, the decomposition of the powders were analyzed using XRD and FTIR analysis, the increasing heat treatment temperature and increasing silver amount were found to negatively effect the decomposition of the powders. The hydroxyapatite powders produced which do and do not contain silver were used to produce coatings on titanium substrates, hydroxyapatite decomposition at high sintering temperatures was effectively inhibited by the use of titanium dioxide inner layer. The effects of coating voltage and coating duration of the titanium dioxide inner layer on the mechanical properties of the coatings were examined, use of lower voltage and shorter coating times for the titanium dioxide inner layer were found to increase the mechanical strength of the coated hydroxyapatite.
Keywords: Hydroxyapatite coating.; Antibacterial agents.